2020
DOI: 10.11591/ijece.v10i1.pp997-1005
|View full text |Cite
|
Sign up to set email alerts
|

Detecting malicious URLs using binary classification through adaboost algorithm

Abstract: Malicious Uniform Resource Locator (URL) is a frequent and severe menace to cybersecurity. Malicious URLs are used to extract unsolicited information and trick inexperienced end users as a sufferer of scams and create losses of billions of money each year. It is crucial to identify and appropriately respond to such URLs. Usually, this discovery is made by the practice and use of blacklists in the cyber world. However, blacklists cannot be exhaustive, and cannot recognize zero-day malicious URLs. So to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…Similar to these studies, there are many other studies such as in ( Guz et al, 2010 , Jabri et al, 2018 , Khan et al, 2020 ). All these studies aim to show the power of AdaBoost algorithm, especially in binary classification problems.…”
Section: Related Worksupporting
confidence: 73%
“…Similar to these studies, there are many other studies such as in ( Guz et al, 2010 , Jabri et al, 2018 , Khan et al, 2020 ). All these studies aim to show the power of AdaBoost algorithm, especially in binary classification problems.…”
Section: Related Worksupporting
confidence: 73%
“…AdaBoost was used as classifier method to detect malicious URLs. They showed that AdaBoost algorithm gave more accuracy than other algorithms [24]. c) Gradient boosting Gradient boosting was a model that used decision trees to train several trees together, in which each decision tree learned from previous tree errors, resulting in greater accuracy in prediction.…”
mentioning
confidence: 99%
“…2D or 3D convolutional layers are typically utilized with the pictures. However, a 1D convolutional layer has been employed to work with text, which has shown to be highly successful, mainly when dealing with time-series or sequence data [ 39 , 40 ]. CNN reduces the requirement for manual features extraction because the network learns the features immediately.…”
Section: Methodsmentioning
confidence: 99%